Green HRM In Improving Employee Performance By Mediating Role Of Green OCB And Green Behavior: Study On Manufacturing Companies In Singapore - Fery Riyanto; Amron Amron; Jamanto Sujipto (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2023)
This study examined the effect of green human resource management (GHRM) and organizational performance on Singapore's ELPRO Steel Conduit and Cable Support System Manufacturing Industry. This study introduced Green Behavior and Green OCB (Organizational Citizen Behavior) as mediating variables. This study uses a quantitative method. Data analysis used Partial Least Square (PLS) with smart-PLS3 software. The study population was Blue Pearls Pte Ltd Manufacturing Industry, Singapore's ELPRO steel conduit and cable support employees, with 106 respondents using the census sample method. The results showed that all the hypotheses tested were accepted. GHRM significantly impacts employee performance through the dominant factor of employee involvement in environmentally friendly practices. Meanwhile, Green Behavior and Green OCB can indirectly mediate GHRM on employee performance. The results of this research can provide insights for organizational to develop policies, programs and practices that encourage the adoption of GHRM, green Behavior and green OCB of employees and improve employee performance in their organization.